The Existence of Social Capitals and their Contribution to the Empowerment of Roasted Peanut as a Small Industry in Indonesia - Widiawati Kimbal, Rahel; Negeri Manado, Universitas (International Journal of Engineering and Technology, 2018)
This research paper is intended to share the identification of (1) various problems of Roasted peanut as a small industry, (2) Negative forms of social capital that hamper the business activities of small industry and (3) Positive forms of social capital which accelerate the business activities of roasted nut as a small industry In Indonesia, taking the case of the small industry in one of the producers of roasted peanut in eastern region that is North Sulawesi particularlyÂ Kanonang Kawangkoan.This research uses qualitative research method with case study. Data collection technique in this research is triangulation which involves observation, interview and documentation. Spradley model is used to analyze data.The results of the research reveal various problems in small industry as follows: (1) The lack of capital, (2) Seasonal-depending production, (3) Traditional processing, (4) Simple Saprodi, (5) Low Production Quality Control (6) Limited information on market, (7) low bargaining power, (8) inadequate information about market, (9) Tight Competition, (10) Lack of Innovation, (11) No patent rights.The development of this industry is hampered by negative social capital emerging from the destructive behavior of some people who seek for more profit, which becomes the main obstacle for this small industry to develop. However, various forms of social capital have ability to anticipate these obstacles. Positive social capital found in roasted nut as a small industry is built from family network or trust-based friendship in which reciprocity is fostered based on prevailing values and norms in the society. The existence of this social capital becomes a main reason for the sustainability of roasted peanuts as a small industry business; therefore, it ensures that farmers and entrepreneurs to continue taking part in the business world.Â Â